Analysis of the Relationship of General Anxiety Disorders, Symptoms of Depression and Sleep Quality with Mental Health of the Elderly During the Covid-19 Pandemic in Semarang City (Universitas Negeri Semarang, 2022)
The Covid-19 pandemic is a new form of case in the world of health that has various impacts, both biological, psychological, social and spiritual. Conditions like this must really be watched out for, especially at the vulnerable age and at risk, one of which is the elderly. Anxiety, depression and sleep disorders in the elderly are psychiatric disorders and are mental health problems that often occur among the elderly. The purpose of this study was to analyze the relationship between general anxiety, depressive symptoms and sleep quality with mental health. This research is an analytic observational study with a cross sectional approach. The population of this study is all the elderly in the city of Semarang whototaling 164.532 elderly.The sample used is 110 respondents withpurposive sampling technique based on the inclusion and exclusion criteria that have been determined. The research instrument used is a questionnaire. The data analysis in this study were univariate analysis (frequency distribution), bivariate analysis (rank Spearman correlation test) and multivariate analysis (multiple regression test). The results showed that there was a significant relationship between generalized anxiety disorder and symptoms of depression with mental health during the Covid-19 pandemic in the elderly in Semarang City. There is no relationship between sleep quality and mental health during the Covid-19 pandemic in the elderly in Semarang City.